Evolution of M23C6 phase in HR3C steel aged at 650 °C. (3rd May 2016) - Wang, Wei; Wang, Zhiwu; Li, Wensheng; Tian, Jing; Zhong, Wanli; Lin, Jiedong
Abstract: The evolution of the morphology, composition, and particle size of the M23 C6 phase in HR3C steel aged at 650 °C was analysed, by means of metallographic microscopy, scanning electron microscopy, and transmission electron microscopy. The results showed that the Cr/Fe ratio in the M23 C6 phase, in the form of irregular square and long strip, increased with the ageing time. Fe was gradually replaced by Cr in the M23 C6 lattice. The M23 C6 phase gradually evolved and then became stable after ageing for 2000 h.